Pengaruh Kebiasaan Menyikat Gigi Sebelum Tidur Malam Hari Terhadap Status Gingiva Pada Siswa Sekolah Dasar Kelas I Dan V - Amani Nabila Fitri; Hidayati Hidayati; Kosno Suprianto (Faculty of Dentistry Universitas Andalas, 2019)
The low level of public awareness causes a negative impact on oral health, especially for children. The bad effects that can occur are gingivitis. One of the factors that cause gingivitis is plaque. Therefore, this study wanted to determine whether the habit of brushing teeth before sleeping at night had an effect on gingival status. The purpose of this study was to determine the effect of brushing teeth before going to bed at night on gingival status in grade IV and V students of SDN 08 Parak Gadang Barat, Padang, Prov. West Sumatra. This type of research is analytical with aresearch design cross sectional. The number of research samples was 34 children. The data collection method was conducted by interviewing and checking the gingival status using the Gingival Index according to Loe and Silness. Based on the results of the study, it was found that 55.9% of respondents had mild gingivitis and 52.9% of respondents had a habit of not regularly brushing their teeth at night before going to bed. Then, based on the results of thebivariate analysis Chi-Square, it was found that the habit of brushing teeth before going to bed at night with gingival status (p <0.05). The conclusion of this study was that the habit of brushing your teeth at night before going to bed affected the gingival status.